Comparison of actual evaporation from water surface measured by GGI-3000 evaporimeter with values calculated by the Penman equation - KOHUT, Mojmír; ROŽNOVSKÝ, Jaroslav; KNOZOVÁ, Grazyna (Contributions to Geophysics and Geodesy, 2014)
Information about water evaporation is essential for the calculation of waterbalance. Evaporation, however, is a very complex physical process and it is thereforedifficult to quantify. Evaporation measurements from the weather station network of theCzech Hydrometeorological Institute between 1968 and 2011 were performed using theevaporimeter GGI-3000. Evaporation was calculated using modified standard methodbased on FAO. The aim of the article was to compare the measured values and calculations.It has been found that the evaporation values from water surface calculatedusing the empirical equation are usually higher than the measured values by on average0.8 mm, in extreme cases even 6.9 mm. The measured data shows higher variability thanthe calculated values, which means that correlations between series are not strong, thecorrelation coefficient being 0.7. Nevertheless the findings can be used for homogenizationof series measured by the GGI-3000 evaporimeter.